The Impact of Fiscal Measures Adopted in the Period 2019-2022 on the Consolidated State Budget at the Level of the City of Galati - Cristina Elena Badiu (Cazacu) (Risk in Contemporary Economy)
The influence of the pandemic on the Consolidated General Budget was manifested by the increase in the need for financial liquidity to cover the medical and social expenses related to the pandemic, an aspect that made the Consolidated General Budget vulnerable with an effect on the budget deficit, which during the pandemic recorded increases above the level of the deficit from the years before the pandemic. The purpose of this paper is to study the impact that the legislative changes related to the period of the pandemic crisis had on the receipts of the Consolidated State Budget, both at the macroeconomic level and at the level of the city of Galati. The study analyzed the evolution of the collection of the main types of income to the state budget, namely VAT, corporate and income tax and social contributions. The increasing value of these indicators shows that the fiscal measures adopted had a positive effect on the economy as a whole. From the analysis of the data taken from the Galati County Administration of Public Finances, it can be observed that the taxes studied had a positive evolution in the last 2 post-pandemic years, registering higher levels than in 2019.